2005
DOI: 10.1590/s1516-635x2005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytase in laying hen diets with different phosphorus sources

Abstract: An experiment was conducted to evaluate the effects of the enzyme phytase in diets formulated with different phosphorus sources on performance, eggshell quality and excretion of commercial laying hens. Two hundred and eighty-eight commercial Hyssex Brown laying hens were evaluated during two production phases, which included eight twenty-eight-day cycles, using a completely randomized design in a 3x2 factorial with six replicates of eight birds per treatment. Three phosphorus sources (calcium and sodium phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, other authors did not find any significant influence of microbial phytase supplementation on commercial layer performance (Casartelli, et al 2005;Liebert et al, 2005), although it has already been shown that the effect of phytase supplementation can be changed by dietary Ca levels (Lim et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, other authors did not find any significant influence of microbial phytase supplementation on commercial layer performance (Casartelli, et al 2005;Liebert et al, 2005), although it has already been shown that the effect of phytase supplementation can be changed by dietary Ca levels (Lim et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…However, in the present experiment, P balance (PB) was lower, which was expected because the diets containing phytase had lower total P content. According to Liebert et al (2005), the addition of phytase to layer diets did not affect P excretion, whereas Casartelli et al (2005) found reduced P, Ca and N excretion with 1000 PhU/ kg. Considering that the level of available P was similar among the experimental diets, the results confirm the Table 4 -Ca intake, excretion and balance expressed in g/day and as intake percentage, Ca in the eggshell (g/day and intake percentage) and Ca body balance (mg/day of brown layers fed diets containing different calcium levels and the addition or not of phytase and/or sodium butyrate between 40 and 44 weeks of age.…”
Section: Fi(g/d) Fcr(kg/dz) Fcr(kg/kg) Epr(%) Aew(g) Es%mentioning
confidence: 96%
“…The interaction between the level of the phytase and non-phytate phosphorus showed that phytase increased egg production in the chickens with a diet containing 0.25% phosphorus but not in the chickens using a diet with 0.15% non-phytate phosphorus and 4.0% Ca. Casartelli et al [ 41 ] assayed the effect of phytase (0 and 100 FYT/kg) in diets including various sources of phosphorus and calcium (Ca and sodium phosphate, microgranulated di-Ca phosphate, and triple superphosphate). They showed that the application of the phytase significantly affected the egg production traits.…”
Section: Discussionmentioning
confidence: 99%
“…Rations with a lower protein and phosphorus content contribute to lower feed prices, but also result in the excretion of nitrogen, phosphorus and other potential polluters of the environment (Nahm and Carlson, 1998). Another feasible alternative to reduce the negative environmental impacts of poultry manure, especially when it is meant to be used as a fertiliser, is the use of the enzyme phytase (Casartelli et al, 2005). It has been shown that the use of phytase may not only release P but also other nutrients including energy and protein (Silversides and Hruby, 2009), which makes it possible to reduce the mineral and protein ingredients in the complete feed.…”
Section: Introductionmentioning
confidence: 99%